Situs beranibersuara.id sebagai Bentuk Psikoedukasi Pencegahan dan Penanganan Kekerasan Seksual Berbasis Sistem Informasi - Aisyah Syihab; Bambang Riono Arsad; Maharani Ardhi Putri; Bernadeth Hani Nuringtyas Sri Mumpuni; Jihan Shabrina Feby Amelia; Bitara Fifi Fayyaza Arge; Nia Amanda Putri; Syammi Arya Sufi Wijaya; Muhammad Naufal Fauzi; Rizky Aprilliansyah; Shaka Mutaqin Arrifku (Fakultas Psikologi Universitas Pancasila, 2024)
Various efforts have been made to prevent and address sexual harassment in higher education environments, yet it still occurs. One approach is through psychoeducation. Therefore, an information system was designed as a form of psychoeducation that can be accessed anytime and anywhere to prevent and address sexual harassment, called beranibersuara.id. This information system includes several features to help survivors and prevent sexual harassment. These features are the psychoeducational module regarding sexual harassment, a “Call Us” feature that enbles survivors to get help quickly from the task force or police, and a counselor feature for psychological assistance. There is also a health reference feature that provides a list of hospitals, including their addresses and telephone numbers, for survivors to check their health after experiencing sexual harassment. This information system also provides mindfulness psychoeducation and training videos to reduce negative emotions experienced by survivors. Based on the results of the usability test of the berabibersuara.id site (18-20 January, 2024) involving 55 participants, 58,2% stated that features on the site were usable. However, maintenance and development of this site are needed as media for psychoeducation on the prevention and handling of sexual harassment.